ANALISIS STRATEGI PENGEMBANGAN USAHA TANI BAWANG MERAH DI LEMBANG PULU’-PULU’ KECAMATAN BUNTU PEPASAN KABUPATEN TORAJA UTARA - Abedneigo Carter Rambulangi; Althon K Pongtuluran; Dina Ramba; Wilma Dian Ardiyanti (Journal of Management Small and Medium Enterprises (SMEs), 2023)
There are a variety of challenges that onion farmers in Lembang Pulu-Pulu, Buntu Pepasan District, North Toraja Regency confront in establishing their shallot farming business, including marketing, capital, and farmers' knowledge. As a result, the purpose of this research is to establish the strategy for improving shallot cultivation in Lembang Pulu'-Pulu', Buntu Pepasan District, North Toraja Regency. This study used a qualitative technique with IFAS, EFAS, and SWOT analysis. The findings of the plan for growing shallot farming in Lembang Pulu'-Pulu', Buntu Pepasan District, North Toraja Regency, including 1) Improving the quality of human resources for shallot merchants. 2) Establishing commercial agreements with multiple significant corporations and financial institutions to receive financing. 3) Increasing shallot output in Lembang Pulu'-Pulu' by utilizing more advanced farming technologies. 4) Using digital communication technologies to broaden the marketing network. Keywords: Strategy; Farming; SWOT; EFAS; IFAS